Elderly Gymnastics Affects Lowering Blood Pressure in Hypertension - Helmi, Alfian; Syafei, Zakirullah; Lina, Lina; Azwarni, Azwarni; Hayani, Nora; Isneini, Isneini (Poltekkes Kemenkes Aceh, 2024)
Background: Hypertension can be prevented and controlled by cultivating a healthy lifestyle by consuming balanced nutritious food, exercising regularly, getting enough rest, thinking positively, not smoking, and not consuming alcohol. However, the lack of adequate knowledge about hypertension and its prevention tends to increase the incidence of hypertension. Regular exercise such as elderly gymnastics is highly recommended to prevent the elderly from getting chronic diseases such as hypertension. Purpose: To determine the effect of elderly gymnastics on reducing blood pressure in hypertension sufferers at Puskesmas Karang Baru Aceh Tamiang. Methods: The study showed that there was a difference in the average measurement of systolic blood pressure, namely that the average blood pressure after doing elderly gymnastics was lower than those who did not do elderly gymnastics with the p value in both groups being the same, namely 0.031 (p <0.05). Results: The study showed that there was a difference in the average measurement of systolic and diastolic blood pressure, namely that the average blood pressure after doing elderly gymnastics was lower than those who did not do elderly gymnastics with a p value of 0.031 (p <0.05). Conclusion: There is a significant difference in the decrease in blood pressure in the elderly who do elderly gymnastics and those who do not. Elderly gymnastics that is done regularly has a positive impact, namely it can reduce blood pressure in the elderly who have hypertension.